Vision, Mission And Objectives Of Education In Hadith Perspective - Julhadi Julhadi (Ambarsa : Jurnal Pendidikan Islam, 2022)
The vision and mission of Islamic education in the hadith are not only as slogans or as decorations and school wall displays, but really must be used as the basis for bringing the educational institution towards improvement accompanied by innovations in it. The very basic goal of Islamic education is to create human beings to become true servants of Allah. That is to make his whole life devoted only to Allah SWT. Besides that, the purpose of Islamic education is to create a balanced life between the life of the world and the hereafter. Islamic education also aims to develop human potential to become a perfect human being (insan kamil).